Protein denaturation: importance in the dairy industry (Research, Society and Development, 2020)
Milk is a food that has unique and essential properties for the human diet. Its processing can increase the range of products offered on the market, decrease costs and facilitate transportation and storage, and can also increase service life. Milk proteins are ingredients that are most valued for their excellent nutritional, technological and functional properties. Heat treatments are applied to raw milk for a variety of purposes, including maintaining public health through the elimination of pathogens and deteriorating microorganisms and the inactivation of enzymes and / or the coagulation of cellular proteins. However, the application of heat causes reversible and irreversible chemical changes that directly affect the final product. The interest in protein denaturation has remained constant over the years, and research on the subject continues to be carried out, which is why the relevance of understanding the structure and factors that affect micellar stability and how to control this process takes place. The article briefly describes the structure of milk and its properties, emphasizing the treatments that can be applied in order to denature proteins and their applications in the dairy industry. It is concluded that the stability of these proteins is an important factor to guarantee adequate processing conditions, increase the useful life of dairy products and provide higher quality to the final consumer, in addition to having great commercial importance, as it is one of the best sources of protein to feed.